Implementation of Problem Based Learning Assisted by Learning Management System to Improve Students' Mathematical Communication Skills - Adi Candra Kusuma; Almas Adibah; Gillang Al Azhar; Edi Sulistio Budi (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2023)
Learning is not limited to the transfer of knowledge, but rather needs to provide opportunities for students to communicate ideas clearly in order to develop more flexible and practical abilities. The aim of the research is to determine the implementation of Problem Based Learning assisted by a Learning Management System (LMS) to improve students' mathematical communication skills. The research method uses a quantitative type, with a sample of class 1F of 23 students as the experimental class and class 1G of 24 students as the control class for the 2022/2023 even semester academic year in the D4 Electronics Engineering study program at the Malang State Polytechnic. Data collection methods such as observation and tests, where instruments are provided with observation sheets and test questions. Data analysis used the normal test, homogeneous test, proportion test, comparison test (test) and the N-gain test. The research results show that the data is normally distributed and homogeneous. The research indicators meet 1) Students' ability to communicate mathematics which is influenced by the treatment given through Problem Based Learning with the help of LMS reaches the minimum standard in learning both (B) individual and classical, exceeds 75%, 2) Students' ability to communicate mathematics which is influenced by the treatment given through Problem Based Learning with LMS support is better than expository learning, 3) The increase in mathematical communication skills of students who take part in Problem Based Learning with LMS support is significantly higher than expository learning, namely 0.496 in the medium category.